Queue size estimation of nodes in a heterogeneous ocean network with multiple priority traffic. (4th May 2020) - Simi, S.; Ramesh, Maneesha Vinodini; Ushakumari, P.V.
Ocean network is a heterogeneous wireless network of fishing vessels at sea to provide internet over sea. The types of messages exchanged between fishing vessels include emergency data, normal data, voice and video messages. As the connectivity is intermittent, it is necessary to select the most appropriate message from the transmission queue for forwarding. This paper focuses on designing a queuing model with multiple priorities to estimate the queue size of each type of message in a node. Solving the steady state equations gives the number of emergency packets, data packets, audio packets and video packets waiting in the node to be transmitted. Hence the message dissemination algorithm can select the appropriate queue for transmitting the message to maximise the available resources with fairness.